Dynamic model and analysis of nonlinear vibration characteristic of a curve-face gear drive - Cai, Zhiqin (Strojniški vestnik, 2017)
To study the nonlinear dynamic characteristics of curve-face gear drive, a generalized nonlinear dynamic model based on Lagrange Bond- graphs was presented. The model considered the effects of the basic parameters of curve-face gear, such as meshing frequency, eccentricity k and the order number n 1 of non-cylindrical gears. Utilizing this simulation model, the vibration characteristics of curve-face gears were analysed. It is indicated that the vibration response of the curve-face gear is more complex than that of the face gear due to the influence of external excitation. These characteristics determine that this gear pair cannot be applied directly to a transmission system with high speed. Finally, a related experiment was proposed to present the validation of the numerical model.
Keywords: časovno odvisne lastnosti; grafi povezav; Lagrangeova metoda; omejena hitrost; vibracijski odziv; zobniki